Unique Image Characteristics of an Occipital Primary Chondroblastic Osteosarcoma: A Rare Case Report and a Brief Literature Review - He, Xin; Yuan, Tingting; Yan, Yuzhu; Yu, Jinlu; Tong, Dan (Journal of Neurological Surgery Reports, 2017)
Primary osteosarcomas of the skull and skull base are rare and comprise < 2% of all skull tumors. In head and neck osteosarcomas, the chondroblastic subtype occurs most frequently, which has an exceedingly poor outcome, but its image characteristic remains unknown. Herein, we report a case in the right occipital bone of the skull base and the unique characteristics of image. Pathologic examination of the surgical specimens led to the diagnosis of chondroblastic osteosarcomas. We believe those image characteristics can improve the understanding of skull chondroblastic osteosarcoma and the preoperative diagnosis.
Keywords: chondroblastic osteosarcoma; occipital bone; skull base; computed tomography; magnetic resonance imaging